PERANCANGAN PROMOSI CAFE SARANG GAGAK MELALUI MEDIA LUAR RUANG - LEON YANSEN, Dra. Jupriani, M.Sn., Drs. Suib Awrus, M.Pd. (DEKAVE : Jurnal Desain Komunikasi Visual, 2016)
At the time of this cafe is one of the business is very high demand, seen from the habits of young people today who like Hangout, .yaitu gathered to just talk in the cafe, with the advent of this habit, the cafe became one of the favorite places for children young to socialize.Cafe nest crow's own stand, to facilitate social of young people, as a place to gather and relax, cafe crow's nest has a strategic place to be on the highway, and in addition Talago, atmosphere Talago those enjoyed by people as a place to enjoy nature because of the beautiful scenery who was in the cafe. But to introduce this cafe crow's nest requires a promotion.From this analysis, the authors found that one medium that is very good and effective are billboards, because billboard huge outdoor media that could attract the attention of the target audience, and is considered an excellent fit with the strategic areas owned by the crow's nest cafe. By using SWOT analysis method Media support used is the x-banner, menu books, key chains, stickers, cards, flags and paper cup chain.With the completion of the design of this crow's nest cafe promotion, expected to provide penambahaan visitors to the cafe..Keyword: Cafe, Promosi, Baliho